Conceptualization and Parts of the Body in Quechua in the s. XVII - Faucet Pareja, Carlos Alberto (2020)
In this paper I aim to describe the way body parts were conceptualized by early seventeenth century Quechua speakers, Also I intend to show the conceptualization of metaphoric and metonymic expressions in which body parts were involved. The corpus analyzed here is constituted by the Huarochirí manuscript(1608) and the Cotahuasi letters (1616), both of textual nature.